Description of Streptomyces naphthomycinicus sp. nov., an endophytic actinobacterium producing naphthomycin A and its genome insight for discovering bioactive compounds - Kaewkla, Onuma; Perkins, Mike; Thamchaipenet, Arinthip; Saijuntha, Weerachai; Sukpanoa, Sudarat; Suriyachadkun, Chanwit; Chamroensaksri, Nitcha; Chumroenphat, Theeraphan; Franco, Christopher Milton Mathew (Frontiers in Microbiology, 2024)
Endophytic actinobacteria are group of bacteria living inside plant tissue without harmful effects, and benefit the host plant. Many can inhibit plant pathogens and promote plant growth. This study aimed to identify a strain of Streptomyces as a novel species and study its antibiotics production. An endophytic actinobacterium, strain TML10T was isolated from a surface-sterilized leaf of a Thai medicinal plant (Terminalia mucronata Craib & Hutch). As a result of a polyphasic taxonomy study, strain TML10T was identified as a member of the genus Streptomyces. Strain TML10T was aerobic actinobacterium with well-developed substrate mycelia with loop spore chains and spiny surface. Chemotaxonomic data, including cell wall components, major menaquinones, and major fatty acids, confirmed the affiliation of strain TML10T to the genus Streptomyces. The results of the phylogenetic analysis, including physiological and biochemical studies in combination with a genome comparison study, allowed the genotypic and phenotypic differentiation of strain TML10T and the closest related. The digital DNA-DNA hybridization (dDDH), Average nucleotide identity Blast (ANIb), and ANIMummer (ANIm) values between strain TML10T and the closest type strain, Streptomyces musisoli CH5-8T were 38.8%, 88.5%, and 90.8%, respectively. The name proposed for the new species is Streptomyces naphthomycinicus sp. nov. (TML10T =TBRC 15050T =NRRL B-65638T). Strain TML10T was further studied for liquid and solid-state fermentation of antibiotic production. Solid-state fermentation with cooked rice provided the best conditions for antibiotic production against methicillin-resistant Staphylococcus aureus. The elucidation of the chemical structures from this strain revealed a known antimicrobial agent, naphthomycin A. Mining the genome data of strain TML10T suggested its potential antibiotic producer of valuable compounds such as ε-Poly-L-lysine (ε-PL) and arginine deiminase. Strain TML10T contain arcA gene encoding arginine deiminase and could degrade arginine in vitro.